Memorial dedicated to Lieutenant Colonel Charles Burton Burr - Ghosh, Ayan (2023)
Memorial dedicated to Lieutenant Colonel Charles Burton Burr, who died in 1821. He played a significant role in the defeat of the Peshwa Army during the Battle of Kirkee on 5 November 1817, during the Third Anglo-Maratha War (1817-1819). The barefoot soldier on the right is wearing the uniform of the 1st Battalion, 7th Regiment of the Bombay Native Infantry, which Charles Burton Burr commanded.